Kesenjangan Sosial antara Pedagang Perempuan Etnis Melayu dan Tionghoa - Eraskaita Ginting; Yusnaini Yusnaini (Society, 2020)
People in Jambi city assume that Pasar Hong Kong, a traditional market located in Jelutung sub-district, is “a Chinese market”, even some areas in the city of Jambi such as Jelutung, Koni, and Talang Banjar are dominated by the ethnic of Chinese. This research aims to explore how social inequality that occurs due to the advantages and disadvantages of an ethnic group so that it can affect individual attitudes that damage social capital. This research uses a case study approach with in-depth interviews and literature study as data collection techniques. The subjects of this study were ethnic Malay and Chinese female merchants in Pasar Hong Kong, Jambi city, Indonesia. This research found that social inequalities that occur among the female merchants of ethnic Malay and Chinese in Pasar Hongkong occur naturally, where both merchants and buyers have a high tolerance when interacting. Although sometimes there are differences in attitude when the merchants serve different ethnic buyers. The involvement of traditional leaders in managing social inequalities is very important due to the lack of assimilation among ethnic Malay and Chinese.